Effect of phenolic compound-protein covalent conjugation on the physicochemical, anti-inflammatory, and antioxidant activities of silk sericin. (June 2022) - Omar, Adil; Arken, Amina; Wali, Ahmidin; Gao, Yanhua; Aisa, Haji Akber; Yili, Abulimiti
Abstract: Sericin, as an inexpensive byproduct of the silk industry, has drawn increasing attention due to its good biocompatibility and various bioactivities. Covalent interactions between proteins and phenolic compounds are ubiquitous and can affect the functional properties of proteins, but little is known about the interactions between sericin and phenolic compounds. In our research, hydroquinone and pyrogallol were selected as model phenolic compounds to investigate the interaction between sericin and phenolic compounds. UV spectroscopy and SEC-HPLC confirmed that sericin and oxidized phenolic compounds formed conjugates, which were primarily the result of covalent interactions. The covalent binding of phenolic compounds changed the secondary structure and thermal behavior of sericin and increased its surface hydrophobicity. The covalent interaction had a positive effect on the emulsifying activity of sericin. Likewise, the antioxidant activity and anti-inflammatory activity of sericin were enhanced in the presence of phenolic compounds. Sericin-phenolic conjugates would be used as multifunctional ingredients in cosmetics, food, and other industries due to their improved emulsifying, antioxidant, and anti-inflammatory properties. Graphical Abstract: ga1 Highlights: Sericin was modified with hydroquinone and pyrogallol. Covalent binding of phenolics changed the physicochemical properties of sericin. Covalent interaction had a positive effect on the emulsifying activity of sericin. Antioxidant activity of sericin was enhanced in the presence of phenolics. Anti-inflammatory activity of sericin was enhanced in the presence of phenolics.